Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd001141.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Support for healthy breastfeeding mothers with healthy term babies

Abstract: Background There is extensive evidence of important health risks for infants and mothers related to not breastfeeding. In 2003, the World Health Organization recommended infants be exclusively breastfed until six months of age, with breastfeeding continuing as an important part of the infant’s diet till at least two years of age. However, breastfeeding rates in many countries currently do not reflect this recommendation. Objectives To assess the effectiveness of support for breastfeeding mothers. Search me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
361
2
25

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(401 citation statements)
references
References 200 publications
(477 reference statements)
13
361
2
25
Order By: Relevance
“…A recent Cochrane review of support for breastfeeding mothers with healthy term babies found that support from both professionals and lay supporters increased the duration; however, support offered reactively, which was initiated only after women sought out contact instead of on an ongoing, scheduled basis, was not effective. 24 They concluded that face-to-face support at scheduled visits was optimal.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review of support for breastfeeding mothers with healthy term babies found that support from both professionals and lay supporters increased the duration; however, support offered reactively, which was initiated only after women sought out contact instead of on an ongoing, scheduled basis, was not effective. 24 They concluded that face-to-face support at scheduled visits was optimal.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Mistrust of health care providers among Black women is well-documented and has been correlated with inadequate access to continuous care. [21] Renfrew MJ, et al [22] pointed out that when breastfeeding support is only offered reactively and women have to initiate the contact, it is unlikely to be effective. The reverse is also true.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 Cochrane Review of 52 randomized breastfeeding support trials (totaling 56,451 women) found that mothers who were encouraged by health care providers to breastfeed were less likely to stop breastfeeding at four months after birth. [7] "Encouragement" was defined broadly to include reassurance, praise, information, the opportunity to discuss and respond to mothers' questions, and staff training. Study neither identified nor addressed the optimal timing of provider encouragement.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, from a staffing standpoint, nursing personnel should arrange for time to be available to assess and document the status of the infant and infant feeding while the baby is in the family's room. 5,10,41,45,46 (I, II-3, III) 4. Women may need help from healthcare providers to ensure that they are able to position and attach their babies at the breast.…”
Section: Prenatalmentioning
confidence: 99%
“…(I, III) Peer-to-peer support should also be offered and has been proven to be helpful in promoting breastfeeding success. 16,46 (I, I-2)…”
Section: 1347-49mentioning
confidence: 99%